DETERMINATION OF ORTHODONTIC TREATMENT TIME ON MALE CHILD WITH MIXED DENTITION PHASE BASED ON PALATAL MEASUREMENT - Puspita, Dian Nur; Chusida, An’nisaa; H, Bambang Soegeng (International Journal of Psychosocial Rehabilitation, 2026)
Some studies and research showed increasing in palatal dimension in children during the growth period. Orthodontist chooses to do an early orthodontic treatment at this period. The growth of palatal is different between early mixed dentition, late mixed dentition, and permanent dentition. Some orthodontist had argued that early orthodontic treatment gave the best result when the palatal growth occurred. Objective: This research target is to determine the right time to begin early orthodontic treatment in children by measuring palatal height, palatal width, and palatal depth. Methods: This study carried out at SDN Airlangga 2, Surabaya, in September 2011. The total sample is 90 male children, consist of 30 male children with early mixed dentition, 30 children with late mixed dentition, and 30 male children with early permanent dentition. The sample criteria are 8, 10, and 12 years old boys, never get any orthodontic treatment and Javanese people in Surabaya. Palatal height, palatal width, and palatal depth were measured by sample dental cast. Result: The results show there are an increase of palatal height, palatal width, and palatal depth as the growth of the age, but the differences are not significant. Conclusion: This research concludes that early orthodontic treatment can be held during the mixed dentition period.